2008
DOI: 10.1116/1.2998807
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oxygen on growth and properties of diamond thin film deposited at low surface temperature

Abstract: Polycrystalline diamond thin films are grown on a p-type Si (100) single crystal substrate at a low surface deposition temperature of 455°C using a microwave plasma enhanced chemical vapor deposition process in an Ar-rich Ar∕H2∕CH4 plasma containing different oxygen levels from 0% to 0.75%. The surface deposition temperatures are measured and monitored by an IR thermometer capable of working in a plasma environment without any interference from the plasma emissions. The lower surface deposition temperature at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…This is also supported by recent observations in Ref. 19 i.e., the growth orientation varied from /1 1 1S to /1 1 0S by adding oxygen in reaction gases of CH 4 and H 2 . However, at a high B-flow rate (20 sccm), the [1 1 1] texture is re-dominated in the corresponding product.…”
Section: Resultssupporting
confidence: 83%
“…This is also supported by recent observations in Ref. 19 i.e., the growth orientation varied from /1 1 1S to /1 1 0S by adding oxygen in reaction gases of CH 4 and H 2 . However, at a high B-flow rate (20 sccm), the [1 1 1] texture is re-dominated in the corresponding product.…”
Section: Resultssupporting
confidence: 83%
“…Hence we introduced CO 2 into the reaction gas mixture to enhance the etching effect at low substrate temperatures by oxygen. [17][18][19] We applied a water cooled substrate holder to maintain the substrate below 100°C. The substrate temperature was monitored by a K-type thermocouple in contact with the substrate surface.…”
Section: Methodsmentioning
confidence: 99%
“…It can be observed that intensities of C 2 , CH, Hα radicals decrease in Fig.7. Meanwhile, the band at 400-405nm gradually disappears with O 2 addition and emissions at 390nm become stronger, indicating the amount increase of CO present in the plasma [25]. The decrease rate of C 2 radicals is much larger than that of CH and radicals.…”
Section: Epitaxial Growth Of the Single Crystal Diamondmentioning
confidence: 95%
“…In Fig.9, dependence of and on O 2 concentration is shown and it is found that rises firstly and then falls with increasing O 2 concentration. It is because that O 2 will react with CH radicals preferentially under low concentration of O 2 [25]. With increasing O 2 concentration, the consumption of CH radicals reaches saturation.…”
Section: Epitaxial Growth Of the Single Crystal Diamondmentioning
confidence: 99%